Indonesia’s efforts to tackle Illegal, Unreported, and Unregulated (IUU) fishing in Arafura and Timor Seas through the Arafura Timor Seas Ecosystem Action (ATSEA) - Salsabila, Wangi; Apriwan; Dermawan, Rifki (Hubungan Internasional Universitas Andalas, 2024)
Abstract This research analyzes Indonesia’s efforts to tackle Illegal, Unreported, and Unregulated (IUU) fishing in Arafura and Timor Seas through the Arafura Timor Seas Ecosystem Action (ATSEA). The Arafura and Timor Seas are one of the Indonesian waters with the highest cases of IUU fishing. Indonesia then joined regional cooperation through the Arafura Timor Seas Ecosystem Action (ATSEA). This is done by Indonesia to protect Arafura and Timor Seas’ maritime security. The author uses the concept of maritime security by Christian Bueger and Timothy Edmunds who have two components consist of Organizing Maritime Security and Managing Complexity and Governing Maritime Security Abroad: Capacity Building and Security Sector Reform (SSR). The research methodology employed is qualitative, utilizing a descriptive analytical approach and relying on secondary data. This research found that Indonesia's joining the ATSEA program had a significant impact on overcoming IUU fishing in the Arafura and Timor Seas. Indonesia’s efforts show some achievements in terms of law, security, cooperation, and knowledge. Keywords: ATSEA, IUU fishing, Indonesia, Arafura and Timor Seas